UTILIZING THE LOCAL POPULATION IN GUARDING AND PROTECTING THE STATE BORDER - Narziqulov , Murodullo (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
The article analyzes the importance of engaging the local population in the protection and safeguarding of state borders. It examines the role of people living in border areas in ensuring security, as well as the mechanisms of information exchange and cooperation. The research findings demonstrate the effectiveness of this approach and identify existing challenges.